If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8a + -1c = 2(pi) * r Multiply ip * r 8a + -1c = 2ipr Solving 8a + -1c = 2ipr Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'c' to each side of the equation. 8a + -1c + c = c + 2ipr Combine like terms: -1c + c = 0 8a + 0 = c + 2ipr 8a = c + 2ipr Divide each side by '8'. a = 0.125c + 0.25ipr Simplifying a = 0.125c + 0.25ipr
| 2x+y(2x)= | | x-(5x-5)=13 | | 5/6(12x-6)-4(3x-1)=0 | | -5(y-6)=5y-30 | | x-532=-32 | | 12v^2=27+27v | | 19b-10=35b+b | | -18=-24-9-15 | | 6x-6y=-1 | | -2(2x-2)=-4x-4 | | 12x^3-13xy-14y^2= | | -x-(13+4x)=-3(5-9x) | | 19b+10=35b+b | | 1t^2-1=0 | | 2u^2+2u-3=0 | | 3(y+2)=-2(y-3) | | 2x-y(2x)= | | -4x+19=-7(x-4) | | 24=2x+14 | | 3y^3-12y^2+6y-24=0 | | 1.8+7n=5.9-4n | | 18x^3=2x | | h^2+81=3 | | 6x-2=4x+5 | | 64=40+3x | | 4z-5=3 | | -2x^2-8x-14=-6 | | 7(v-5)=4v-47 | | 16a^3b^2+4a^2b^2-12ab-4ab^2= | | x+88=5x+40 | | -12=x-13 | | 2(4+x)-4x-2x=28-6x |